2009
DOI: 10.1139/t09-035
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network (ANN) models for determining hydraulic conductivity of compacted fine-grained soils

Abstract: This study deals with development of artificial neural networks (ANNs) and multiple regression analysis (MRA) models for determining hydraulic conductivity of fine-grained soils. To achieve this, conventional falling-head tests, oedometer falling-head tests, and centrifuge tests were conducted on silty sand and marine clays compacted at different dry densities and moisture contents. Further, results obtained from ANN and MRA models were compared vis-à-vis experimental results. The performance indices such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 78 publications
(65 reference statements)
0
32
0
Order By: Relevance
“…Several learning algorithms have been developed. The back-propagation learning algorithm, the most commonly used neural network algorithm [9,35,[43][44][45][46][47][48], has been successfully applied with to model many phenomena in the field of geotechnical engineering [49][50][51]. In this algorithm, learning is performed through the gradient descent on the sum of the squares of the errors for all the training patterns [43,49].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Several learning algorithms have been developed. The back-propagation learning algorithm, the most commonly used neural network algorithm [9,35,[43][44][45][46][47][48], has been successfully applied with to model many phenomena in the field of geotechnical engineering [49][50][51]. In this algorithm, learning is performed through the gradient descent on the sum of the squares of the errors for all the training patterns [43,49].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Recently, ANNs have been found to be a useful tool to solve many problems in the field of the geotechnical engineering [3]. Since the early 1990s, ANNs have been effectively applied to almost every problem in geotechnical engineering, including constitutive modeling [5,6]; geomaterial properties [3,[7][8][9]; bearing capacity of pile [10,11]; slope stability [12][13][14][15][16]; shallow foundations [17][18][19]; liquefaction potential [20][21][22][23][24][25][26]; and tunnels and underground openings [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Samui (2008) analyzed pore water pressure response through neural network. Erzin et al (2009) studied the hydraulic conductivity of compacted fine grained soils developing ANN and multiple regression analysis (MRA) models. Lim and Kolay (2009) predicted hydraulic conductivity of tropical soils by using ANN and demonstrated a comparison between the conventional estimation of hydraulic conductivity by using Shepard's equation and the predicted hydraulic conductivity from ANN.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, artificial neural networks (ANNs) have played an important role in such fields as aerospace, automotive, telecommunications and transportation (Chaturvedi et al, 2002;Demuth and Beale, 2002;Smith and Demetsky, 1994). In geotechnical engineering, ANNs have been used successfully in the prediction of lateral load capacity of piles (Das and Basudhar, 2006), in the modeling of maximum dry density and optimum moisture content of soil (Alavi et al, 2010) and in determining the hydraulic conductivity of compacted finegrained soils (Erzin et al, 2009). It has been shown that ANNs can be used successfully for the prediction of moisture content of finegrained soil in the shortest time possible (Shetu and Masum, 2012), but this approach suffers from several limitations.…”
Section: Introductionmentioning
confidence: 99%